Study on the influence of Confucianism and corporate governance mechanism on performance - WU, Yujie (Institutional Knowledge at Singapore Management University, 2024)
As the cornerstone of traditional Chinese culture, Confucianism profoundly influences Chinese enterprises' behaviour. This study empirically examines the impact of Confucianism and corporate governance mechanisms on companies' financial and social performance, yielding the following principal conclusions utilizing data from Chinese-listed companies: Firstly, Confucianism significantly and positively influences corporate performance. Enterprises deeply rooted in Confucian culture often exhibit superior financial and social performance. This finding indicates the positive role of Confucianism in promoting responsible corporate behaviours and enhancing performance. Secondly, the impact of corporate governance mechanisms on corporate performance is complex. An increase in institutional ownership correlates positively with corporate performance, suggesting that institutional investors can elevate corporate governance standards through effective oversight. The influence of the proportion of shares held by principal shareholders is more intricate, depending on the regional differences of Confucianism. Thirdly, an interaction exists between Confucianism and corporate governance mechanisms, jointly affecting corporate performance. The positive effects of Confucianism are more pronounced in companies with robust corporate governance structures, especially those with a higher proportion of independent directors. This finding unveils the complementary roles of Confucianism and corporate governance mechanisms in improving corporate performance. Lastly, the study identifies the regional heterogeneity in the interactive effects between Confucianism and corporate governance variables. Companies located near different Confucian centres vary significantly in how Confucianism and their interactions with corporate governance mechanisms impact performance. This suggests that regional cultural backgrounds and the depth of Confucianism directly affect corporate performance and modulate through different corporate governance mechanisms. This finding underscores the importance of acknowledging regional heterogeneity and the complex interplay between Confucianism and corporate governance structures when considering their influence on corporate strategies and performance. By exploring the heterogeneous impacts of Confucianism and corporate governance mechanisms on financial and social performance, this study not only expands the research perspective of the existing literature but also provides new guidance for corporate management practice. Understanding and effectively integrating informal institutions with formal corporate governance mechanisms is crucial for enhancing corporate performance in globalization and multiculturalism.